Folly Beach, South Carolina. Beach Erosion Control and Hurricane Protection. Appendix 2. Revision. - CORPS OF ENGINEERS CHARLESTON SC CHARLESTON DISTRICT (1985)
The recommended plan provides for beach restoration, erosion control and improvement of recreational beach along the ocean shoreline of Folly Beach, South Carolina. The plan improvement provides for restoration and periodic renourishment of a continous reach of beach in the center section of the Folly Island ocean shoreline for a total project length of 16,860 feet. The plan would require 684,000 cubic yards of sandy fill material. Borrow areas selected as a source of fill sand are shoal areas in Lighthouse and Stono Inlets. Beach nourishment and restoration would create and maintain a total of 23 acres of beach which would bring about an increase in recreational activity and reduce beach erosion which currently endangers oceanfront development. Minor and temporary impacts include the disruption of benthic populations, increase in water turbidity, reduction in aesthetic values during construction, possible improvement of the navigability of inlets due to the removal of shoal material and increase in auto emissions and noise levels during peak activity periods. Revision of report dated 28 Mar 80, AD-A115709.